“The Best Kept Secret of the War”: Gendering Societal Citizenship and the Canadian State’s Material Education of British War Brides - Gaudet, Anna (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2025)
This article provides a cultural perspective on the Canadian state’s “repatriation” of British war brides alongside their husbands following the Second World War. It investigates how the government-issued booklets Welcome to War Brides (1944) and Canadian Cook Book for British War Brides (1945) defined “Canadianness” and explores how this definition reflected the contemporary ideas and interests of the Canadian state through a gendered lens. It highlights the ways in which these materials were custom-built for their audience and epoch, revealing the ideological preoccupations of the Canadian state on the eve of postwar social, moral, and economic regeneration by interrogating the concept of a dependent citizen. By promoting women’s domestic and sexual containment, a moral and heteronormative strengthening of the family unit, and the safeguarding of the white, Anglo-Saxon superiority, the linguistic and non-linguistic signifiers of Canadianness communicated through these educative materials provides nuanced insight into the Canadian state’s relationship to British immigrants as a nonlocal yet familiar and trusted other. The conflation of conformity to successful acculturation and good citizenship in these materials enriches discussions about Canadian national identity and the role of the state in the postwar period.